Multi-Risk Assessment in Post-Mining Lignite Areas - Dafni M. Nalmpant-Sarikaki; Alexandros I. Theocharis; Nikolaos C. Koukouzas; Andreas G. Benardos; Ioannis E. Zevgolis (Materials Proceedings)
As Europe addresses decarbonization, huge coal mining areas shall be reclaimed and appropriately valorized, creating the post-mining areas. This work assesses their resilience and safety by methodologically addressing multi-hazards threatening closed and abandoned mines. The current work modifies an indicator-based semi-quantitative multi-hazard method towards post-mining risk assessment, described as the (1) identification of the hazards, (2) assessment of the interactions, and (3) quantification of the level of interactions. The methodology can appropriately quantify the multi-hazard severity for various scenarios. However, it has limitations, not considering appropriately the hazards’ sequence and missing an objective criterion for scenario comparison.